Relevance of colour vision and diabetic retinopathy to self-monitoring of blood glucose. - Graham, K (1980)
A study was performed to determine the effect of colour vision defects and diabetic retinopathy on diabetic patients' ability to use a visual method of measuring their own blood glucose concentrations. Forty-eight diabetics whose colour vision and retinal status was assessed by an ophthalmologist carried out 311 blood glucose estimations using oxidase-peroxidase test strips which were then compared with laboratory values. There was a trend towards poor performance with advancing age but neither colour vision nor diabetic retinopathy had a significant effect on patients' ability to use this visual method of estimating blood glucose concentrations. The vast majority of diabetics who will benefit from being able to monitor their own blood glucose control should have no difficulty in using a visual method of testing, even if they do have defects of colour vision.